2017
DOI: 10.1080/09537104.2017.1293812
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the centrifuge characteristics and centrifugation protocols on the cells, growth factors, and fibrin architecture of a leukocyte- and platelet-rich fibrin (L-PRF) clot and membrane

Abstract: L-PRF (leukocyte- and platelet-rich fibrin) is one of the four families of platelet concentrates for surgical use and is widely used in oral and maxillofacial regenerative therapies. The first objective of this article was to evaluate the mechanical vibrations appearing during centrifugation in four models of commercially available table-top centrifuges used to produce L-PRF and the impact of the centrifuge characteristics on the cell and fibrin architecture of a L-PRF clot and membrane. The second objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
260
1
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 280 publications
(322 citation statements)
references
References 32 publications
8
260
1
13
Order By: Relevance
“…No significant differences were found in the basic haematological confrontation, which had an average concentration of RBC 9. [12] and Dohan Ehrenfest et al [13,14] and those we observed in the horse model. In this comparison, it was verified that there are significant differences in the characteristics of the clot, but these differences are eliminated when the membranes derived from the compression were examined.…”
Section: Resultssupporting
confidence: 64%
“…No significant differences were found in the basic haematological confrontation, which had an average concentration of RBC 9. [12] and Dohan Ehrenfest et al [13,14] and those we observed in the horse model. In this comparison, it was verified that there are significant differences in the characteristics of the clot, but these differences are eliminated when the membranes derived from the compression were examined.…”
Section: Resultssupporting
confidence: 64%
“…17 The ultrastructure of the fibrin membrane evidenced by SEM is a dense and intricate gauze-like mesh, very characteristic of the PRF elastic and resistant membranes. 14,19 It is important to notice that further studies are necessary to confirm that this apparent evidence of stability by direct observation reflects the maintenance on the integrity of the fibrin network, employing techniques such as SEM. 18 The absence of alterations in the size of these membranes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Esta centrifugadora es la única hasta ahora aprobada por la FDA/CE del mercado. Se ha descrito que presenta el menor nivel de vibración (32) y que con ella se obtiene un coágulo de mejor calidad (33) cuando es comparada con otras tres centrifugadoras (A-PRF 12 (Advanced PRF, Process), LW -UPD8 (LW Scientific) y Salvin 1310 (Salvin Dental).…”
Section: Discussionunclassified
“…La Fibrina Rica en Plaquetas (PRF: Platelet Rich Fibrin) surgió en Francia en 2001 (3) como una segunda generación de concentrados plaquetarios con ciertas ventajas sobre el Plasma Rico en Plaquetas (PRP) (4,5) . Este biomaterial no requiere anticoagulantes en su preparación y muestra liberación sostenida de factores de crecimiento durante por lo menos 7 días (6,7) . La PRF contiene una matriz de fibrina con una gran cantidad de plaquetas y leucocitos, elementos clave que actúan en forma sinérgica promoviendo la cicatrización y la regeneración tisular (8) .…”
unclassified